Teacher Education Programmes at Alexandria University with reference to Tuning Methodology - Alsaeed Alshamy (Universidad de Deusto, 2016)
The study aims at using the outcomes of Tuning Africa Project - I to propose implications for policy and practice for enhancing the quality of Teacher Education Programmes in Egyptian higher education. It investigates the views of different stakeholders - academics, students, graduates and employers - who relate to three faculties in charge of Teacher Education at Alexandria University. The study focuses on the generic competences and the key subject-specific competences which future teachers should be acquainted with. The data have been collected through questionnaires administered to 384 participants and through semi-structured interviews with 10 academics. The main findings show that, across all different stakeholders, there are significant gaps for both generic and subject-specific competences between what is deemed important and what is deemed as the level of achievement at Alexandria University. The average ranking for both generic and subject-specific competences was 3.75 in terms of importance but only 2.54 in terms of achievement. This is an indication that effort and intentional strategies needed to be put in place to minimize the gaps of the relevant Teacher Education Programmes. This calls for a paradigm shift from input and staff-centered programmes to output and student oriented ones. In order to achieve such a paradigm shift, several actions concerning policy and practice should be promoted. Among them, the study proposes changing the regulations of existing programmes; revising programmes in order to allow inclusion of the Tuning determined generic and subject-specific competences. The study further proposes raising awareness about the importance of competence-based learning among academics, students, graduates, employers and the society at large as well as involving all stakeholders in the process of curriculum design and quality enhancement. All these are potential in promoting capacity building and training for academics who are equipped to incorporate new competences in the existing programmes/courses. Such academics will be able to initiate new courses with commonly agreed structures; they will be able to incorporate the needed competences in such a way that comparability and equivalence of learning outcomes between Alexandria University and other African universities become possible. Published online: 01 June 2016